ERASMUS+ (2019-1-UK01-KA203-062118) - Saveriades, Alexis (My University, 2026)
Academic Researcher under the Cyprus Partnership in the project entitled - Higher Education Curricula Development on the Collaborative Economy in Europe (Acronym: COLECO) - Project's Budget 216,742.00 Euros